Three new records of species of genera Elaphoglossum (Dryopteridaceae) to Peru - Mellado, L. Franco (2008)
Elaphoglossum lloense, E. murinum, E. neei and E. puberulentum are confirmed and reported for the Peruvian flora, all of which were found in Yanachaga-Chemillén National Park, Oxapampa,Pasco These new records increases to 142 the total number of taxa known in the genus for Peru.